Lessons Learned from the Development Operational Rules for Sustainable Use of Resources: a Case Study on Kogluang Conservation Network Project, Suanmon Sub-district Administrative Organization, ManchaKhiri District, Khon Kaen Province - machamadol, panarat (King Prajadhipok’s Institute Journal, 2020)
This research aims to study the design principle, rules, and the results of the sustainable exploitation of common pool resources (CPR) to enforce the law and to be consistent with national policies. Study the lesson learned to the best practice from the operational rules with the CPR development projects to integrate the operational rules with collective-choice rules and constitutional rules. The research revealed that in the past, the power of natural resource management was vested exclusively with state; lack of public participation led to increasing degradation of natural resources. It is hypothesized that substantial involvement of a community in designing operational rules or communal rules for natural resource management could help community members value the natural resources. The Kogluang Forest Conservation Project in Suanmon Sub-district is examined to draw lessons and identify best practices for CPR development projects to integrate operational rules with collective-choice rules. The design rule at the community level is categorized into two parts: behavior regulation and sanctions. The process of designing the communal rule comprises three steps: (1) consolidation for resolution; (2) creating the communal rule; and (3) collectively establishing a compliance organization for the communal rule. The recommendations of this research are that the government should translate the CPR communal rule in to a national specific CPR rule called “the Common Pool Resource Management Act, B.E …”. At the same time, the governments should public relations with Thai people’s views the right on CPR in public goods, in accompany with implementing compliance the operational rules, and the local governments should survey local people’s needs for informing “rules” and capacity-building for stakeholders. In addition, the provincial authority should formulate a provincial strategy on collaboration in the management of CPR in the inter-provincial area and neighbouring areas.